Determination of toxinotypes of environmental clostridium perfringens by polymerase chain reaction - Florence, L.C.H.; Hakim, S.L.; Kamaluddin, M.A.; Thong, Kwai Lin (2011)
Toxinotype of Clostridium perfringens (CP) isolates collected from the Bernam River, Selangor River and Tengi Canal between April 2007 and January 2008 were determined by Polymerase Chain Reaction (PCR) using published primers. All the 147 isolates were toxinotype Type A, harbouring the alpha toxin gene. In addition, 5 of the isolates also had the enterotoxin (CPE) gene.